Erschließung und Entwicklung der ägyptischen Neulandgebiete - Meyer, Günter (ERDKUNDE, 1978)
After the revolution of 1952 land reclamation was declared to be one of the most important aims of the Egyptian government. Until 1975 about 411 000 hectares were reclaimed, of which 259 000 hectares ar actually cultivated. A considerable proportion of this area is affected by salinity as a result of insufficient drainage. The cultivation of the new lands is mainly done by agricultural state companies and by settlers who own or rent some 1.7 hectares each. Land use pattern, problems of agricultural production and marketing, and the economic situation of the two groups of cultivators are examined in this paper. In order to increase the productivity of the state farms joint ventures with foreign companies have been established. Recently some newly reclaimed areas were distributed to agricultural engineers in plots of 8.4 or 12.6 hectares, while other new lands were sold by auction in plots of up to 42 hectares. So far the agricultural engineers have turned out to be very efficient cultivators whereas the sale of land to mainly urban capitalists is regarded as being anything but favourable for the future development of these newly reclaimed areas.